Rokok Terhadap Pengetahuan Dan Sikap Pada Anak Usia Sekolah Menengah PertamaDi SMPN 5 Kota Bengkulu - Trisna Wulan Safitri; Tita Septi Handayani; Meri Epriana Susanti (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
Tobacco addiction. From a preliminary study of 10 students, data was obtained showing that 7 students admitted to having smoked. Their knowledge of the dangers of smoking was still low for the most part, and their attitudes towards smoking tended to be neutral to positive. The purpose of this study was to determine the effect of health education on the dangers of smoking on the knowledge and attitudes of respondents among students at SPMN 5 Bengkulu City.This study used a quasi-experimental design with a pretest-posttest approach with one group. The target population in this study was 186 students, and the sample consisted of 65 respondents. The data analysis technique used in this study was a paired T-test. The knowledge scores before the health education were that most of the respondents (55.4%) had good knowledge, and after the health education, most of the respondents (76.9%) had good knowledge. The attitude scores before the health education were positive for most of the respondents (63.1%), and after the health education, the attitudes were generally positive for the respondents (90.8%). There was a significant effect between knowledge and attitudes before and after the health education about the dangers of smoking on male students at SMPN 5 Bengkulu City. It is hoped that the findings of this study can be used by the school as information in efforts to increase students' knowledge about the dangers of smoking, provide additional insight for the Faculty of Health Sciences at Dehasen University, serve as a reference for future researchers, and provide respondents with an understanding of the impact of smoking on school-age children.